Expression of c-Fos and c-Jun in the cornea, lens, and retina after ultraviolet irradiation of the rat eye and effects of topical antisense oligodeoxynucleotides. Issue 3 (March 1995) - Gillardon, F; Zimmermann, M; Uhlmann, E
Abstract : AIMS–Immunohistochemical techniques were used to investigate c-Fos and c-Jun proto-oncogene expression in the cornea, lens, and retina after ultraviolet irradiation of the rat eye. METHODS–Eyes of anaesthetised rats were exposed to 1.5 J/cm2 of ultraviolet radiation (280-380 nm). Animals were perfused 1, 6, or 24 hours after irradiation and tissue sections were incubated with specific antiserum to c-Fos and c-Jun, respectively. RESULTS–Non-irradiated contralateral eyes displayed no c-Fos and c-Jun immunoreactivity. One and 6 hours after ultraviolet exposure numerous c-Fos and c-Jun immunopositive nuclei were observed mainly in the epithelial cell layers of the cornea and the lens epithelium. Scattered labelled nuclei were detectable in the retinal ganglion cell layer and the inner nuclear layer. Twenty four hours after irradiation c-Fos and c-Jun protein expression returned to near control levels. Histological signs of ultraviolet damage (for example, chromatin condensation, nuclear fragmentation) were first recognisable in the corneal epithelium 6 hours after irradiation and became more apparent at later times. CONCLUSION–Thus, the rapid and sustained activation of c-Fos and c-Jun expression in the eye after single ultraviolet exposure may represent the molecular mechanism underlying ultraviolet induced photodamage and initiation of cell death. Furthermore, topical application of a c-fos antisense oligodeoxynucleotide to the ultraviolet exposed rat eye inhibited the increase in c-Fos expression in the cornea, suggesting therapeutic activity of antisense drugs in corneal malignant and infectious diseases.